2018
DOI: 10.1002/1878-0261.12382
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical studies reveal that LSD1 inhibition results in tumor growth arrest in lung adenocarcinoma independently of driver mutations

Abstract: Lung adenocarcinoma (LUAD) is the most prevalent subtype of non‐small cell lung cancer. Despite the development of novel targeted and immune therapies, the 5‐year survival rate is still only 21%, indicating the need for more efficient treatment regimens. Lysine‐specific demethylase 1 (LSD1) is an epigenetic eraser that modifies histone 3 methylation status, and is highly overexpressed in LUAD. Using representative human cell culture systems and two autochthonous transgenic mouse models, we investigated inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…LSD1 dysfunction is also associated with the development of ALL (acute lymphoblastic leukemia) and AML (acute myeloid leukemia) [2224]. Preclinical studies have revealed that LSD1 inhibition could suppress tumor growth of lung adenocarcinoma independent on driver mutations [25]. Expression profiling reveals that LSD1 inhibition mainly affects replication machinery and cell cycle, and interrupts downstream signaling of EGFR (epidermal growth factor receptor).…”
Section: Introductionmentioning
confidence: 99%
“…LSD1 dysfunction is also associated with the development of ALL (acute lymphoblastic leukemia) and AML (acute myeloid leukemia) [2224]. Preclinical studies have revealed that LSD1 inhibition could suppress tumor growth of lung adenocarcinoma independent on driver mutations [25]. Expression profiling reveals that LSD1 inhibition mainly affects replication machinery and cell cycle, and interrupts downstream signaling of EGFR (epidermal growth factor receptor).…”
Section: Introductionmentioning
confidence: 99%
“…Many new methods are currently used to diagnose and treat this disease [ 3 ]. Epidermal growth factor receptor (EGFR) and anaplastic lymphoma kinase are two key oncogenes that trigger lung adenocarcinoma (LUAD) [ 4 , 5 , 6 ]. Despite great achievements, overall survival (OS) time for LUAD is less than 5 years because of aggressive properties of the tumor and a lack of effective early diagnostic and prognostic biomarkers [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer can be categorized into two main histological subtypes, non-small-cell lung cancer (NSCLC) and small-cell lung cancer, accounting for ~85% and ~15% of cases, respectively (2,3). Lung adenocarcinoma (LUAD) is one of the major subtypes of NSCLC with a low 5-year survival rate of ~20% in the USA (4,5). It is currently understood that two of the driver oncogenes involved in tumorigenesis and progression of LUAD are epidermal growth factor receptor and anaplastic lymphoma kinase (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%